Distribution D'une Nouvelle Adventice, Porophyllum Ruderale (Asteraceae), Des Cultures De Côte d'Ivoire - Kpla A Christine Florence; Touré Awa; Gué Arsène; Ipou Ipou Joseph (European Scientific Journal, ESJ, 2018)
The presence of Porophyllum ruderale is increasingly recognized in different agroecosystems in Côte d’Ivoire. The current study is initiated to determine its distribution area and abundance. To achieve our goals, data were collected through surveys of farmers and field sampling was conducted to assess the abundance of Porophyllum ruderale. These were processed by the Correspondence Analysis (AC), and with a GPS, geographic coordinates were incorporated into the ArcGIS software to identify colonized areas. Forest regions (Adzopé and Daloa) are the most infested with a centesimal frequency (Fr) of 100% of Porophyllum ruderale. In the other localities (Yamoussoukro, Man, Bondoukou) the frequencies vary from 43 to 93 %. This species is rare in the Korhogo region with a zero centesimal frequency. Agroecological zones favorable to the development of the weed have a rainfall amounting from 1100 to 2400 mm and a temperature between 21- 28 C. Of the various agrosystems encountered, cassava is the crop with the highest presence and the highest density of Porophyllum ruderale with more than 21 individuals / m2 . At the end of this study, Porophyllum ruderale is present in most of Ivorian territory, particularly in forest areas where agriculture is the main activity.